RESEARCH ON FATIGUE CRACK PROPAGATION CHARACTERISTICS AND REMAINING LIFE AT THE TOOTH ROOT OF A GEAR - GAO Yun; YANG LiuQing; LIU Shuai; CHEN WenHua; ZHOU Xun (Jixie qiangdu)
Based on the FEM, the fatigue crack propagation of a involute cylindrical gear is numerically simulated. Firstly, through analyzing the meshing gear of a pair of healthy teeth, the maximum bending stress of the tooth root is determined, And it is taken as the starting point of the crack. The cracks are divided into crack and non crack blocks. The initial crack is preformed in the crack block and the block is remeshed with isoparametric singular element. The crack block and the non cracked block is connected by a multi-point constraint. The stress intensity factor and crack propagation angle are measured in crack propagation process, Based on Paris formula,tooth crack propagation trajectory and remaining life of gear is numerically simulated. The influence of load as well as initial crack length on residual life was analyzed.